Modeling the tumor microenvironment of anaplastic thyroid cancer: an orthotopic tumor model in C57BL/6 mice - Xu, Zhen; Shin, Hyo Shik; Kim, Yoo Hyung; Ha, Seong Yun; Won, Jae-Kyung; Kim, Su-jin; Park, Young Joo; Parangi, Sareh; Cho, Sun Wook; Lee, Kyu Eun (Frontiers in Immunology, 2023)
Introduction: Securing a well-established mouse model is important in identifying and validating new therapeutic targets for immuno-oncology. The C57BL/6 mouse is one of the most fully characterised immune system of any animal and provides powerful platform for immuno-oncology discovery. An orthotopic tumor model has been established using TBP3743 (murine anaplastic thyroid cancer [ATC]) cells in B6129SF1 hybrid mice, this model has limited data on tumor immunology than C57BL/6 inbred mice. This study aimed to establish a novel orthotopic ATC model in C57BL/6 mice and characterize the tumor microenvironment focusing immunity in the model. Methods: Adapted TBP3743 cells were generated via in vivo serial passaging in C57BL/6 mice. Subsequently, the following orthotopic tumor models were established via intrathyroidal injection: B6129SF1 mice injected with original TBP3743 cells (original/129), B6129SF1 mice injected with adapted cells (adapted/129), and C57BL/6 mice injected with adapted cells (adapted/B6).The adapted TBP3743 cells de-differentiated but exhibited cell morphology, viability, and migration/invasion potential comparable with those of original cells in vitro. The adapted/129 contained a higher Ki-67 + cell fraction than the original/129. RNA sequencing data of orthotopic tumors revealed enhanced oncogenic properties in the adapted/129 compared with those in the original/129. In contrast, the orthotopic tumors grown in the adapted/B6 were smaller, with a lower Ki-67 + cell fraction than those in the adapted/129. However, the oncogenic properties of the tumors within the adapted/B6 and adapted/129 were similar.Immune-related pathways were enriched in the adapted/B6 compared with those in the adapted/129. Flow cytometric analysis of the orthotopic tumors revealed higher cytotoxic CD8 + T cell and monocytic-myeloid-derived suppressor cell fractions in the adapted/B6 4 compared with the adapted/129. The estimated CD8 + and CD4 + cell fractions in the adapted/B6 were similar to those in human ATCs but negligible in the original/B6.A novel orthotopic tumor model of ATC was established in C57BL/6 mice.Compared with the original B6129SF1 murine model, the novel model exhibited more aggressive tumor cell behaviours and strong immune responses. We expect that this novel model contributes to the understanding tumor microenvironment and provides the platform for drug development.